Combined [18F]DPA-714 micro-positron emission tomography and autoradiography imaging of microglia activation after closed head injury in mice. Issue 1 (December 2016) - Israel, Ina; Ohsiek, Andrea; Al-Momani, Ehab; Albert-Weissenberger, Christiane; Stetter, Christian; Mencl, Stine; Buck, Andreas; Kleinschnitz, Christoph; Samnick, Samuel; Sirén, Anna-Leena
Abstract Background Traumatic brain injury (TBI) is a major cause of death and disability. Neuroinflammation contributes to acute damage after TBI and modulates long-term evolution of degenerative and regenerative responses to injury. The aim of the present study was to evaluate the relationship of microglia activation to trauma severity, brain energy metabolism, and cellular reactions to injury in a mouse closed head injury model using combined in vivo PET imaging, ex vivo autoradiography, and immunohistochemistry. Methods A weight-drop closed head injury model was used to produce a mixed diffuse and focal TBI or a purely diffuse mild TBI (mTBI) in C57BL6 mice. Lesion severity was determined by evaluating histological damage and functional outcome using a standardized neuroscore (NSS), gliosis, and axonal injury by immunohistochemistry. Repeated intra-individual in vivo μPET imaging with the specific 18-kDa translocator protein (TSPO) radioligand [18 F]DPA-714 was performed on day 1, 7, and 16 and [18 F]FDG-μPET imaging for energy metabolism on days 2–5 after trauma using freshly synthesized radiotracers. Immediately after [18 F]DPA-714-μPET imaging on days 7 and 16, cellular identity of the [18 F]DPA-714 uptake was confirmed by exposing freshly cut cryosections to film autoradiography and successive immunostaining with antibodies against the microglia/macrophage marker IBA-1. Results Functional outcome correlated with focal brain lesions, gliosis, and axonal injury. [18 F]DPA-714-μPET showed increased radiotracer uptake in focal brain lesions on days 7 and 16 after TBI and correlated with reduced cerebral [18 F]FDG uptake on days 2–5, with functional outcome and number of IBA-1 positive cells on day 7. In autoradiography, [18 F]DPA-714 uptake co-localized with areas of IBA1-positive staining and correlated strongly with both NSS and the number of IBA1-positive cells, gliosis, and axonal injury. After mTBI, numbers of IBA-1 positive cells with microglial morphology increased in both brain hemispheres; however, uptake of [18 F]DPA-714 was not increased in autoradiography or in μPET imaging. Conclusions [18 F]DPA-714 uptake in μPET/autoradiography correlates with trauma severity, brain metabolic deficits, and microglia activation after closed head TBI.